2014
DOI: 10.1007/s00401-014-1354-3
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial fission augments capsaicin-induced axonal degeneration

Abstract: Capsaicin, an agonist of transient receptor potential vanilloid receptor 1, induces axonal degeneration of peripheral sensory nerves and is commonly used to treat painful sensory neuropathies. In this study, we investigated the role of mitochondrial dynamics in capsaicin-induced axonal degeneration. In capsaicin-treated rodent sensory axons, axonal swellings, decreased mitochondrial stationary site length and reduced mitochondrial transport preceded axonal degeneration. Increased axoplasmic Ca2+ mediated the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 80 publications
1
31
1
Order By: Relevance
“…Our results from FCCP/oligomycin suggested that Ca 2ϩ release from mitochondria alone or depolarization of mitochondrial membrane potential was not sufficient to induce ablation of TRPV1-lineage terminals. These results do not exclude a contribution of mitochondria, however, and our data do not necessarily contradict a recent report suggesting a role for mitochondria in capsaicin-induced degeneration of axons (21). Capsaicin increases mitochondrial fission, which, in turn, decreases mitochondrial stationary site sizes in a Ca 2ϩ -dependent manner.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…Our results from FCCP/oligomycin suggested that Ca 2ϩ release from mitochondria alone or depolarization of mitochondrial membrane potential was not sufficient to induce ablation of TRPV1-lineage terminals. These results do not exclude a contribution of mitochondria, however, and our data do not necessarily contradict a recent report suggesting a role for mitochondria in capsaicin-induced degeneration of axons (21). Capsaicin increases mitochondrial fission, which, in turn, decreases mitochondrial stationary site sizes in a Ca 2ϩ -dependent manner.…”
Section: Discussioncontrasting
confidence: 67%
“…On the other hand, it was also suggested that capsaicin depolarizes mitochondrial membrane potential by direct action on mitochondria in sensory neurons (34), which potentially contributes to cytotoxicity. Furthermore, it was recently suggested that Ca 2ϩ -dependent mitochondrial fission augments capsaicin-induced axonal degeneration (21). However, it is still unclear whether mitochondria play a dominant role in capsaicin-induced ablation of nociceptive afferent terminals and how mitochondria contribute to capsaicin-induced axonal ablation.…”
Section: Mitochondrial Dysfunction Is Not a Dominant Contributor To Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of mitochondrial fission support the role of mitochondria [146]. In dissociated DRG neurons, capsaicin induced axonal swelling, which was accompanied by reduction in the length of the mitochondria and motility within axons.…”
Section: Potential Mechanisms Of Vanilloid-induced Chemical Ablatimentioning
confidence: 96%
“…In neurons, hyperglycemia increases Mf and subsequently creates small and damaged mitochondria at this levels, whilst a reduction of Mf increases cellular survival (Edwards et al, ). It was established that inhibition of Ca 2+ ‐dependent Mf facilitates mitochondrial function and axonal surviving in capsaicin‐induced degeneration of rodent sensory axons (Chiang et al, ).…”
mentioning
confidence: 99%